PIMREG expression level predicts glioblastoma patient survival and affects temozolomide resistance and DNA damage response - Serafim, Rodolfo Bortolozo (2022)
PIMREG expression strongly correlates with cellular proliferation in both malignant and normal cells. Throughout embryo development, PIMREG expression is prominent in the central nervous system. Recent studies have described elevated PIMREG expression in different types of tumors, which correlates with patient survival and tumor aggressiveness. Given the emerging significance of PIMREG in carcinogenesis and its putative role in the context of the nervous system, we investigated the expression and function of PIMREG in gliomas, the most common primary brain tumors. We performed an extensive analysis of PIMREG expression in tumors samples from glioma patients. We then assessed the effects of PIMREG silencing and overexpression on the sensitivity of glioblastoma cell lines treated with genotoxic agents commonly used for treating patients and assessed for treatment response, proliferation and migration. Our analysis shows that glioblastoma exhibits the highest levels of PIMREG expression among all cancers analyzed and that elevated PIMREG expression is a biomarker for glioma progression and patient outcome. Moreover, PIMREG is induced by genotoxic agents, and its silencing renders glioblastoma cells sensitive to temozolomide treatment and affects ATR- and ATM-dependent signaling. Our data demonstrate that PIMREG is involved in DNA damage response and temozolomide resistance of glioblastoma cells and further supports a role for PIMREG in tumorigenesis.